Paraguay : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Paraguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2009 Article IV Consultation highlights that the Paraguayan economy performed very well over the past five years, with real GDP growth averaging about 5 percent a year-the best in a generation. The fiscal position strengthened considerably, thereby reducing public debt sharply to relatively low levels. The economy grew by nearly 6 percent in 2008, but growth decelerated in the last quarter of the year. Paraguay's macroeconomic outlook has also been negatively affected by the deterioration in the global environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet